Development of a remote control autonomous mobile robot - Yong, Voon Siew (2003)
Current commercial edutainment robots are expensive, not widely available in the country, and most of the times they have limited features, programmability and functions. This thesis described the design and development of a remote control autonomous mobile robot that enables the studies of robotics controls and its behaviour, such as obstacle avoidance and phototropic behaviour. The proposed robot structure consists of both hardware and software. The hardware comprises of a mobile platform, microcontrollers, motors and sensors. Software provides the programmable brain of the robot to control its entire functions. The robot is designed to be open architecture so that more peripheral can be added. Each of the hardware and software are tested separately, combined as a whole system and test on a few robotic behaviour experiments. The test results meet the thesis objective and it is a successful project. The robot has been constructed, tested and demonstrated in a few public events and the latter proved to be a real crowd puller. In general the proposed robot can be used as a tool for the children to learn and to play.